Future needs and recommendations in the development of species sensitivity distributions: Estimating toxicity thresholds for aquatic ecological communities and assessing impacts of chemical exposures. (29th September 2016) - Belanger, Scott; Barron, Mace; Craig, Peter; Dyer, Scott; Galay‐Burgos, Malyka; Hamer, Mick; Marshall, Stuart; Posthuma, Leo; Raimondo, Sandy; Whitehouse, Paul
ABSTRACT: A species sensitivity distribution (SSD) is a probability model of the variation of species sensitivities to a stressor, in particular chemical exposure. The SSD approach has been used as a decision support tool in environmental protection and management since the 1980s, and the ecotoxicological, statistical, and regulatory basis and applications continue to evolve. This article summarizes the findings of a 2014 workshop held by the European Centre for Toxicology and Ecotoxicology of Chemicals and the UK Environment Agency in Amsterdam, The Netherlands, on the ecological relevance, statistical basis, and regulatory applications of SSDs. An array of research recommendations categorized under the topical areas of use of SSDs, ecological considerations, guideline considerations, method development and validation, toxicity data, mechanistic understanding, and uncertainty were identified and prioritized. A rationale for the most critical research needs identified in the workshop is provided. The workshop reviewed the technical basis and historical development and application of SSDs, described approaches to estimating generic and scenario‐specific SSD‐based thresholds, evaluated utility and application of SSDs as diagnostic tools, and presented new statistical approaches to formulate SSDs. Collectively, these address many of the research needs to expand and improve their application. The highest priority work, from a pragmatic regulatory point of view, is to develop a guidance of best practices that could act as a basis for global harmonization and discussions regarding the SSD methodology and tools. Integr Environ Assess Manag 2017;13:664–674. © 2016 SETAC Key Points: Species sensitivity distributions (SSDs) are probability models that summarize variation of species sensitivities to chemical exposure. SSDs are used in risk assessment and the derivation of environmental quality standards, because they can be used to develop community‐level thresholds and have advantages over deterministic assessment approaches. The 2014 ECETOC and UK Environment Agency workshop summarized research needs to expand and improve application of SSDs. The highest priority work is to develop a guidance of best practices to drive global harmonization and discussions regarding SSD methodology and tools.